MANAJEMEN MUTU PEMIMPIN DAN KEPEMIMPINAN KONTEMPORER BAGI PENINGKATAN PERGURUAN TINGGI KEAGAMAAN DI ABAD XXI - Lumintang, Stevri Indra (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2019)
The objective of this research was to analize deeply and objectively the contemporary management quality of some leaders and their leadership at religiousity higher educations in Indonesia for finding a model of quality improvement the higher education. This research was based upon the naturalistic paradigm with qualitative approach, and the said methodology was a phenomenologic method, by using Ishikawa Fishbone Diagram as a technical tool to improve the quality. The datas were colleted through participant observation using interview, and document study. The data analysis and interpretation indicate that: (1) The real problem is the weak management quality; (2) The weak management quality is caused by the weak leaders and leadership. This main factor influences other factors, just as all influence one and another; (3) The root of weak management quality is caused by the weak leader and leadership. The findings lead to the recommendation to practice quality improvement, and to apply the model of quality improvement, in order for it be one of the quality religiousity higher education in this 21st century.